Number of genes and base composition of mitochondrial tRNA from Saccharomyces cerevisiae. - Schneller, J M (1975)
Increasing amounts of mitochondrial [32P] tRNA (4S fraction), were hybridized with mitochondrial DNA OF Saccharomyces cerevisiae. At saturation, the calculated number of genes for 4S mitochondrial RNA was 20. Mitochondrial [32P] tRNA eluted from the hydrids obtained either with an excess of tRNA or an excess of DNA showed, after alkaline hydrolysis and chromatography, a G+C content of 28 and 35 p. cent respectively. This last value is similar to that found with the total 4S fraction. The odd nucleotides T (about 1T per sequence), U, hU are present in mitochondrial tRNA. Some sequence may begin with pG.